2017
DOI: 10.1007/s11356-017-8848-1
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinus officinalis L. ameliorates titanium dioxide nanoparticles and induced some toxic effects in rats’ blood

Abstract: Titanium dioxide nanoparticles (TiO NPs) have been widely used as a white pigment in food and drugs. The most important route of human exposure to TiO is through food and drug products containing TiO additives. This study investigates the efficacy of an oral traditional use of rosemary extract in ameliorating some toxic effects induced on blood of TiO NP-intoxicated rats. Rats were given rosemary extract via intragastric administration 1 h before the intragastric administration of 100 mg/kg/day TiO NPs (10 nm)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…It has been supported that ethanolic extract of R. officinalis possesses anti-inflammatory ef-fects through decreasing the levels of COX-2, prostaglandin E2, IL-1β, and MMP2 in chronic constriction injury-induced neuropathic pain in rats [17]. Furthermore, R. officinalis aqueous extract diminished the level of IL-6 in TiO2 NP-induced toxicity in rats [18]. Medicherla et al suggested that R. officinalis extract (50 and 100 mg/kg) attenuated COX-2 and inducible nitric oxide synthase expressions, TNF-α and IL-6 levels, and myeloperoxidase activity in dextran sulfate sodium-induced experimental murine colitis.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It has been supported that ethanolic extract of R. officinalis possesses anti-inflammatory ef-fects through decreasing the levels of COX-2, prostaglandin E2, IL-1β, and MMP2 in chronic constriction injury-induced neuropathic pain in rats [17]. Furthermore, R. officinalis aqueous extract diminished the level of IL-6 in TiO2 NP-induced toxicity in rats [18]. Medicherla et al suggested that R. officinalis extract (50 and 100 mg/kg) attenuated COX-2 and inducible nitric oxide synthase expressions, TNF-α and IL-6 levels, and myeloperoxidase activity in dextran sulfate sodium-induced experimental murine colitis.…”
Section: Discussionmentioning
confidence: 94%
“…It has been reported that the ethanolic extract of R. officinalis raises CAT and SOD levels as well as reduces the MDA level following the acute model of intestinal damage induced by ethanol [28]. Grissa et al demonstrated that the aqueous extract of R. officinalis improves SOD, TAS, and CAT activity and prevents MDA and IL-6 levels following TiO2 NPs-induced toxicity in rat blood [18]. Furthermore, Amaral et al reported that R. officinalis ethanolic extract made a significant decrement in MDA, oxidized dichlorofluorescein, and NO levels as well as enhances GSH, CAT, 100.000…”
Section: Discussionmentioning
confidence: 99%
“…Titanium dioxide nanoparticles (TiO2 NPs) as food or drug additives are used in whitening and brightening agents (Yang et al, 2014). It has been demonstrated that rosemary aqueous extract could ameliorate the systemic toxicity of titanium dioxide nanoparticles in rats (Grissa et al, 2017). TiO2 NPs subchronic exposure (100 mg/kg BW via gavage, for 60 days) produced metabolic imbalance (hyperlipidemia, hyperglycemia, and body weight loss) in rats.…”
Section: Titanium Dioxidementioning
confidence: 99%
“…TiO2 NPs subchronic exposure (100 mg/kg BW via gavage, for 60 days) produced metabolic imbalance (hyperlipidemia, hyperglycemia, and body weight loss) in rats. Rosemary extract treatment (5 mL/kg BW via gavage 1 h before the TiO2 NPs administration) decreased glucose and serum lipid levels and significantly enhanced body weight after 8 weeks of treatment (Grissa et al, 2017). Moreover, the rosemary extract could inhibit oxidative stress and DNA fragmentation‐induced by TiO2 NPs‐ in peripheral blood leukocytes (Grissa et al, 2017).…”
Section: Chemical Agents Induced Toxicitymentioning
confidence: 99%
“…TiO 2 NPs of 5-nm size were used to induce poikilocytes, as related studies have shown that the NPs affect the vascular system and damage liver function. 7,8,[16][17][18] Raman spectroscopy is a vibrational spectroscopic method that provides information on the chemical bonds in the sample and is applicable to many fields, including biomedicine. 19,20 There is an increasing number of studies using Raman spectroscopy to examine blood and biomolecules, [21][22][23][24] including in the presence of NPs such as nanodiamonds.…”
Section: Introductionmentioning
confidence: 99%